2022
DOI: 10.2147/tcrm.s349900
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphism in the 3’ Untranslated Region of PRKAA2 on Cardiometabolic Parameters in Type 2 Diabetes Mellitus Patients Who Received Metformin

Abstract: Purpose This study aimed to explore the association of rs857148 A>C as 3ʹUTR variants with blood pressure, HbA1c profile, and lipid profiles as cardiometabolic parameters among patients with T2DM receiving metformin. Patients and Methods This cross-sectional analytic research was conducted with 114 consecutively selected patients with T2DM. Polymerase chain reaction-restriction fragment length polymorphism was conducted to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In the last 30 years, the prevalence of T2DM has doubled, making it one of the most significant global health issues 35 , suggesting the urgent need to identify novel biomarkers for early diagnosis of this endocrine disease. Genetic variations located in the intronic region 36 or the 3′-Untranslated Region (UTR) 37 , 38 of some genes have been found to independently contribute to the predisposition to T2DM, suggesting that there may be other, as-yet-undiscoverable functional variations in Homo sapiens . Additional in-depth population genetic research will be required to comprehend the connection between more complicated haplotypes and disease development in various geographical areas 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last 30 years, the prevalence of T2DM has doubled, making it one of the most significant global health issues 35 , suggesting the urgent need to identify novel biomarkers for early diagnosis of this endocrine disease. Genetic variations located in the intronic region 36 or the 3′-Untranslated Region (UTR) 37 , 38 of some genes have been found to independently contribute to the predisposition to T2DM, suggesting that there may be other, as-yet-undiscoverable functional variations in Homo sapiens . Additional in-depth population genetic research will be required to comprehend the connection between more complicated haplotypes and disease development in various geographical areas 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Malaysia involving 320 volunteers classified based on hypertension (163) and normotensive (157) conditions showed that TT genotype/T allele of the WNK4 gene resulted in a close relationship between hypertension and T2DM 11 . While genetic study remained limited in Indonesia, it is been documented that polymorphism of rs87148, especially CC genotype and C allele, and CAPN10 had a significant association with HbA1c level and increased T2DM vulnerability, respectively 12 , 13 .…”
Section: Discussionmentioning
confidence: 99%
“…By study conducted in Taiwan on 922 participants, 30 novel single nucleotide polymorphisms (SNPs) were associated with comorbid hypertension in T2DM patients adjusted for age and body mass index www.nature.com/scientificreports/ documented that polymorphism of rs87148, especially CC genotype and C allele, and CAPN10 had a significant association with HbA1c level and increased T2DM vulnerability, respectively 12,13 .…”
Section: Discussionmentioning
confidence: 99%